2007
DOI: 10.1158/1535-7163.mct-06-0397
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a potent and selective small-molecule inhibitor of the PIM1 kinase

Abstract: The pim-1 kinase is a true oncogene that has been implicated in the development of leukemias, lymphomas, and prostate cancer, and is the target of drug development programs. We have used experimental approaches to identify a selective, cell-permeable, small-molecule inhibitor of the pim-1 kinase to foster basic and translational studies of the enzyme. We used an ELISA-based kinase assay to screen a diversity library of potential kinase inhibitors. The flavonol quercetagetin (3,3 ¶,4 ¶,5,6,7-hydroxyflavone) was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 33 publications
6
130
0
1
Order By: Relevance
“…Indeed, small molecule inhibitors of the Pim-1 kinase have been recently described in vitro and in cell-based systems. [33][34][35] Targeting the Pim-1 kinase may be a beneficial addition to a traditional cancer chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, small molecule inhibitors of the Pim-1 kinase have been recently described in vitro and in cell-based systems. [33][34][35] Targeting the Pim-1 kinase may be a beneficial addition to a traditional cancer chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 99%
“…118,122 The second class of PIM inhibitors does not interact with the hinge region by forming classical hydrogen bonds and can therefore be considered as ATP competitive but not ATP mimetic inhibitors. This non-canonical binding mode has been first identified for pyrazolo [1,5-a]pyrimidines and the related imidazo[1,2-b]pyridazine (compound 4) and LY294002 (data not shown), initially described as a potent phosphatidylinositol 3-kinase inhibitor.…”
Section: -121mentioning
confidence: 99%
“…These inhibitors display anticancer activity in prostate cancer cell lines, including those that are sensitive and resistant to chemotherapy (11). Despite the fact that the Pim-1 kinase inhibitors that have been investigated exhibit potential anticancer effects, there are a few small molecule inhibitors showing an inhibitory effect (25). In addition, other studies revealed that a Pim-1 specific monoclonal antibody markedly Table II.…”
Section: Discussionmentioning
confidence: 99%